1992
DOI: 10.1038/ki.1992.305
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal, five year survey of urea kinetic parameters in CAPD patients

Abstract: This study reports on the five years' evolution of the KT/V urea index and protein catabolic rate (PCR) in 16 CAPD patients who were treated with a constant daily dialysis dose. Total KT/V urea index decreased with time from a value of 0.96 +/- 0.06 at the start to 0.55 +/- 0.05 at five years of treatment. This decline was due to the opposite changes of two important parameters affecting the index. First, the contribution of the residual urinary KT/V gradually decreased from 28.6% at the start to 8 to 9% after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(78 citation statements)
references
References 8 publications
4
72
1
1
Order By: Relevance
“…Five exchanges/ 19,20 the residual renal function often being negligible after 2 years 16 and zero result in total creatinine clearances greater than 70 L/ at 4 years. 4 There is, however, great variation among most patients with high or high average peritoneal permeability, as indicated in Table 4 (g) and(h). patients in the rate of loss of residual renal function.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five exchanges/ 19,20 the residual renal function often being negligible after 2 years 16 and zero result in total creatinine clearances greater than 70 L/ at 4 years. 4 There is, however, great variation among most patients with high or high average peritoneal permeability, as indicated in Table 4 (g) and(h). patients in the rate of loss of residual renal function.…”
Section: Introductionmentioning
confidence: 99%
“…14 Lameire et al, 4,11 patients who have a very small BSA. Moreover, a prescription of 4×2.5 L also results in inadequate total reported negative correlations between Kt/V urea and the number of days of hospitalization, peritonitis rates solute clearance in patients with a large BSA and low or low average peritoneal transport rates.…”
Section: -15mentioning
confidence: 99%
See 2 more Smart Citations
“…For an anuric 70-kg person, a 12-L drain volume per day would produce a weekly Kt/V of 2.0. Observational studies, using either univariate (3)(4)(5) or multivariate statistical analyses (6,7), suggested that a weekly Kt/V of 1.9 to 2.1 was associated with better patient survival than lower Kt/V values. The Canada-USA (CANUSA) study of incident patients (7) assumed that renal and peritoneal clearances were equivalent and additive with respect to clearance of small solutes.…”
mentioning
confidence: 99%